An Analytical Study of the Reality of Education and Learning in the Light of the Use of E-Learning Platforms for the Students of the Faculty of Physical Education and Sport Sciences at University of Misan - MOHSIN ABED, MURTADHA; DHEYAA ABDLRASOL, MOHAMED; HADI MOUSA, ADNAN (International Journal of Psychosocial Rehabilitation, 2020)
E-learning has achieved encouraging results in the learning process during the Corona pandemic and under the difficult circumstances that the student is going through. The most important problem facing the students is the weakness of the Internet and the power outage, and directing the real problem in the programs of the electronic platforms, although the students had confirmed the need for some educational lectures for educational platforms. The e-education articles are the most effective and best of the theory of the process. The students do not prefer electronic tests and prefer to continue the electronic education after the end of the invasive CK. The instructors take into account the conditions for the students as much as possible because of the invasive CK. There is a need for noncompliance with the specific time when giving lectures and electronic commerce. Urge teachers to diversify the presentation of lectures, especially the process, such as the presentation of video clips or the recording of manual lectures and other means of suspense and effects that serve the learning process.